Application of Material Judgment Monitoring The TBR Plant Division Uses RFID and MES (Manufacturing Execution System) Methods - Andriyani, Fitri; Setiadi, Ade; Alfiah, Fifit (Journal Sensi: Strategic of Education in Information System, 2025)
With great advances in the world of information technology in the industrial era 4.0, efficiency and accuracy in the production process are crucial factors to increase the company's competitiveness. One of the important aspects is material monitoring, especially in the material judgement process in the TBR Plant (Truck and Bus Radial) Division, which requires an information system that supports the material assessment, starting from the hold process, judgement, making reports on the results of the TBR judging plant monitoring to superiors. This study aims to design and develop a material judgement monitoring application based on RFID (Radio Frequency Identification) technology integrated with the MES (Manufacturing Execution System) system to unravel errors in data control, inaccurate reports, and delays in finding the required data are all the results of manual systems. With the application of RFID, every material can be tracked in real time from the inspection process to the production line. Integration with MES enables data synchronization between production systems and enterprise information systems, supporting fast and accurate decision-making. The results of the implementation show an increase in the efficiency of material recording time, the accuracy of data judgement, and the reduction of human error in the tracking process. This application is expected to be an effective digital solution in supporting a more transparent, efficient, and digitized production system in the manufacturing industry environment.